New perspectives in palliative care - Pessini, Leo; Bertachini, Luciana (Acta Bioethica, 2006)
This paper examines palliative care under diverse aspects. After a historical and conceptual review, the question of which health care interventions must be done in the geriatric and gerontology context is examined, as well as their contribution to the maintenance and rescue of functional capacities. We reaffirm the importance of ethical, scientific, humane, spiritual and socio cultural reflection about programs addressed to the health care of elderly in their multidimensional coverage. Finally, we point out some challenges with respect to rescuing the wisdom of living and the dignity of dying.